Appetite, appetite hormone and energy intake responses to two consecutive days of aerobic exercise in healthy young men. (1st September 2015) - Douglas, Jessica A.; King, James A.; McFarlane, Ewan; Baker, Luke; Bradley, Chloe; Crouch, Nicole; Hill, David; Stensel, David J.
Highlights: Repeated exercise on two days did not stimulate appetite or energy intake. Consecutive days of exercise did not elicit compensatory appetite hormone responses. Acute exercise elevated circulating levels of total PYY. Abstract: Single bouts of exercise do not cause compensatory changes in appetite, food intake or appetite regulatory hormones on the day that exercise is performed. It remains possible that such changes occur over an extended period or in response to a higher level of energy expenditure. This study sought to test this possibility by examining appetite, food intake and appetite regulatory hormones (acylated ghrelin, total peptide-YY, leptin and insulin) over two days, with acute bouts of exercise performed on each morning. Within a controlled laboratory setting, 15 healthy males completed two, 2-day long (09:00–16:00) experimental trials (exercise and control) in a randomised order. On the exercise trial participants performed 60 min of continuous moderate-high intensity treadmill running (day one: 70.1 ± 2.5% VO2 peak, day two: 70.0 ± 3.2% VO2 max (mean ± SD)) at the beginning of days one and two. Across each day appetite perceptions were assessed using visual analogue scales and appetite regulatory hormones were measured from venous blood samples. Ad libitum energy and macronutrient intakes were determined from meals provided two and six hours into each day and from a snack bag provided in-between trial days. Exercise elicited a high level of energy expenditure (total = 7566 ± 635 kJ across the two days) but did not produce compensatory changes in appetite or energy intake over two days (control: 29, 217 ± 4006 kJ; exercise: 28, 532 ± 3899 kJ, P  > 0.050). Two-way repeated measures ANOVA did not reveal any main effects for acylated ghrelin or leptin (all P  > 0.050). However a significant main effect of trial ( P  = 0.029) for PYY indicated higher concentrations on the exercise vs. control trial. These findings suggest that across a two day period, high volume exercise does not stimulate compensatory appetite regulatory changes.